UPAYAPENGGALIAN DAN PEMANFAATAN ZAKAT MELALUI BAZIS - Mulatto Mulatto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2006)
Zakat, Infaq and Sodaqoh are strategic Islam institution for empowering economic people. In Indonesia, management ofzakat, infaq and sodaqoh have not been managed goodly. There are some institutions effort to manage the ZIS fund and use its, but in generally management ofthe ZIS more locally and partially. The purpose ofthis research is to know: (I) the professional of management of the zakat, infaq and sodaqoh, in term of system, procedure and manpower; (2) getting alternative formula for managing zakat, infaq and sodaqoh more effective, professional, and accountable; (3) the distribution of zakat, infaq, and sodaqoh fund clearly, and productive. The method of this research use the policy research. The data gathering technique by interview, documentary analyses and observation. The location of this research is in Kudus, Banjamegara and Banyumas. The result of this research are : (I) The managementofZakat, infaq and Sodaqoh in each area is different, especially inplanning and supervisory aspect.(2) The management ofthe zakat, infaqand sodaqoh have no followed the basic management yet.